Soft Material‐Enabled, Active Wireless, Thin‐Film Bioelectronics for Quantitative Diagnostics of Cervical Dystonia. Issue 10 (16th August 2019) - Kwon, Young‐Tae; Lee, Yongkuk; Berkmen, Gamze Kilic; Lim, Hyo‐Ryoung; Scorr, Laura; Jinnah, Hyder A.; Yeo, Woon‐Hong
Abstract: Recent advances in flexible materials, nanomanufacturing, and system integration have provided a great opportunity to develop wearable flexible hybrid electronics for human healthcare, diagnostics, and therapeutics. However, existing medical devices still rely on rigid electronics with many wires and separate components, which hinders wireless, comfortable, continuous monitoring of health‐related human motions. Advanced materials and system integration technologies are introduced that enable soft, active wireless, thin‐film bioelectronics. This low‐modulus, highly flexible wearable electronic system incorporates a nanomembrane wireless circuit and functional chip components enclosed by a soft elastomeric membrane. It can be gently and seamlessly mounted on the skin, while offering comfortable, highly sensitive and accurate detection of head movements. The wireless, skin‐like bioelectronic system (SKINTRONICS) is utilized for quantitative diagnostics of cervical dystonia (CD), which is characterized by involuntary abnormal head postures and repetitive head movements, sometimes with neck muscle pain. A set of analytical and experimental studies shows a soft system packaging, hard–soft materials integration, and quantitative assessment of physiological signals detected by the SKINTRONICS. In vivo demonstration, involving 10 human subjects, finds the device feasible for use in CD measurement. Abstract : Advanced materials and system integration technologies that enable soft, wireless bioelectronics are introduced. A highly flexible wearable electronic system is fabricated from a nanomembrane wireless circuit and functional chip components. Bioelectronics mounted on the skin offer highly accurate detection of head movements. An in vivo pilot study with human subjects investigates using the device for quantitative evaluation of cervical dystonia.